Dibenzodiazepine Derivative Quetiapine- and Olanzapine-Induced Chronic Interstitial Nephritis. (June 2013) - He, Liyu; Peng, Youming; Fu, Xiao; Chen, Xiaogang; Liu, Hong
<x xml:space="preserve">Abstract</x> The dibenzodiazepine derivative is a so-called "atypical" or second-generation antipsychotic that is widely regarded as one of the most effective drug treatments for schizophrenia and depression. Quetiapine and olanzapine are novel atypical antipsychotic agents that possess much improved tolerability. To the best of our knowledge, FDA has reported three cases of olanzapine-induced interstitial nephritis. Yet there have been no known clinical reports that associate quetiapine treatment with chronic interstitial nephritis (CIN). Here, we report the occurrence of CIN in the presence of edema during quetiapine and olanzapine therapy.